Reflectance confocal microscopy and its role in the follow‐up of a topical treatment for lentigo maligna - Coco, Valeria; Perino, Francesca; Di Stefani, Alessandro; Cappilli, Simone; Peris, Ketty (International journal of dermatology, 2021)
Background In recent years, there has been an ongoing interest in topical treatment for lentigo maligna (LM) as imiquimod 5% cream owing to the localization of this tumor and the advanced age of patients; however, the efficacy of imiquimod 5% cream is controversial, and the rate of local relapses is about 25–53%. Reflectance confocal microscopy (RCM) is a noninvasive diagnostic tool useful not only for diagnostic purpose but also for monitoring the response to the local treatment of LM. Our aim was to demonstrate the role of RCM in the follow‐up of a topical treatment with imiquimod 5% cream in clinical practice. Methods We report three patients with histopathologically confirmed LM who were not candidates for surgery and were successfully treated with imiquimod 5% cream. In such patients, dermatoscopic images and reflectance confocal microscopy were useful to evaluate treatment response and to verify long‐term clinical benefits during the follow‐up visits. Results No relapses were observed in our patients 18 months after the end of treatment; although, continuous follow‐up visits are needed in these patients. Conclusions In the case series presented herein, we highlight the importance of RCM as a noninvasive tool to monitor the efficacy of imiquimod to treat LM during and after treatment. Detailed confocal images of two of our patients allowed us to establish the persistence of atypical cells and to continue treatment, although clinical and dermatoscopic examinations showed “apparent complete remission” after the first cycle of therapy.